Antireflux mucosectomy (ARMS) and antireflux mucosal ablation (ARMA) for gastroesophageal reflux disease: a systematic review and meta-analysis - Rodríguez de Santiago, Enrique; Sanchez-Vegazo, Carlos Teruel; Peñas, Beatriz; Shimamura, Yuto; Tanabe, Mayo; Álvarez-Díaz, Noelia; Parejo, Sofía; Kazuya, Sumi; Marcos-Carrasco, Natalia; Vazquez-Sequeiros, Enrique; Inoue, Haruhiro; Albillos, Agustín (Endoscopy International Open, 2021)
Background and study aims Antireflux mucosectomy (ARMS) and antireflux mucosal ablation (ARMA) are new endoscopic procedures for patients with gastroesophageal reflux disease (GERD). We conducted a meta-analysis to systematically assess the feasibility, clinical success, and safety of these procedures.Patients and methods We searched Embase, PubMed, and Cochrane Central from inception to October 2020. Overlapping reports, animal studies, and case reports were excluded. Our primary outcomes were clinical success and adverse events (AEs). Secondary outcomes included technical success, endoscopic esophagitis, 24-hour pH monitoring, and proton pump inhibitor (PPI) use. A random effects model was used to pool data.Results In total, 15 nonrandomized studies (12 ARMS, n = 331; 3 ARMA, n = 130) were included; 10 were conducted in patients with refractory GERD. The technical success rate was 100 %. The pooled short-term (first assessment within the first 6 months), 1-year, and 3-year clinical success rates were 78 % (95 % confidence interval [95 %CI] 70 %–85 %), 72% (95 %CI 47 %–92 %), and 73 % (95 %CI 65 %–81 %), respectively. ARMS and ARMA yielded similar clinical success. The proportion of patients off PPIs at 1 year was 64 % (95 %CI 52 %–75 %). There were significant drops (P < 0.01) in validated clinical questionnaires scores, presence of esophagitis, and acid exposure time. The most common AE (11 %, 95 %CI 8 %–15 %) was dysphagia requiring dilation (7%, 95 %CI 5 %–11 %). Four cases of perforation were recorded, all in patients undergoing ARMS.Conclusions Our meta-analysis of nonrandomized studies suggests that ARMS and ARMA are safe and effective for patients with GERD.